2014
DOI: 10.1098/rstb.2013.0162
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity in multiple sclerosis and in experimental autoimmune encephalomyelitis

Abstract: Approximately half of all patients with multiple sclerosis (MS) experience cognitive dysfunction, including learning and memory impairment. Recent studies suggest that hippocampal pathology is involved, although the mechanisms underlying these deficits remain poorly understood. Evidence obtained from a mouse model of MS, the experimental autoimmune encephalomyelitis (EAE), suggests that in the hippocampus of EAE mice long-term potentiation (LTP) is favoured over long-term depression in response to repetitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 68 publications
(123 reference statements)
0
44
0
Order By: Relevance
“…Results from clinical studies suggest that neuronal damage or neuronal loss critically contributes to functional deficits in MS patients. Of note, there is evidence that neuronal structures are not "simply" destroyed but in parallel neuronal plasticity is impaired in the CNS of MS patients (98). Virtually every element of the neuron can be damaged or even destroyed during gray matter demyelination including cell soma (82,108), dendritic spines (64), synapses (37,91,137) and neurites (108).…”
Section: What Triggers Neurodegeneration In Ms: Pathology Of the Nawmmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from clinical studies suggest that neuronal damage or neuronal loss critically contributes to functional deficits in MS patients. Of note, there is evidence that neuronal structures are not "simply" destroyed but in parallel neuronal plasticity is impaired in the CNS of MS patients (98). Virtually every element of the neuron can be damaged or even destroyed during gray matter demyelination including cell soma (82,108), dendritic spines (64), synapses (37,91,137) and neurites (108).…”
Section: What Triggers Neurodegeneration In Ms: Pathology Of the Nawmmentioning
confidence: 99%
“…Virtually every element of the neuron can be damaged or even destroyed during gray matter demyelination including cell soma (82,108), dendritic spines (64), synapses (37,91,137) and neurites (108). Of note, there is evidence that neuronal structures are not "simply" destroyed but in parallel neuronal plasticity is impaired in the CNS of MS patients (98).…”
Section: What Triggers Neurodegeneration In Ms: Pathology Of the Nawmmentioning
confidence: 99%
“…In support of this hypothesis, pharmacological blockade of glutamate receptors in rodent models of MS (experimental autoimmune encephalitis (EAE)), perturb disease progression and severity, reduce neurological deficits and decrease damage to axons and myelinating cells (oligodendrocytes), despite having no effect on CNS inflammation [151,152]. Furthermore, in acute brain slices from EAE models it has been shown that LTP is enhanced and LTD is reduced, leading to an overall hyperexcitable environment, similar to the human cortex [153][154][155].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…A similar sequence of events may give rise to cognitive impairment in multiple sclerosis. Studies using the EAE rat model of multiple sclerosis show that release of IL-1β from infiltrating lymphocytes or activated microglia facilitates hippocampal long-term potentiation via inhibition of GABA-mediated synaptic activity and increased likelihood of glutamate-mediated excitotoxicity (Nisticó et al, 2013a(Nisticó et al, , 2013b. In contrast, Aβ inhibits induction of NMDA receptor-dependent long-term potentiation in hippocampal slices, and deficiency of iNOS or inhibitors of NADPH oxidase both relieved this inhibitory effect, implicating microglia-derived oxidants (Wang et al, 2004).…”
mentioning
confidence: 99%